Consideration of sex and gender in Cochrane reviews of interventions for preventing healthcare-associated infections: a methodology study - Jesús López-Alcalde; Elena Stallings; Sheila Cabir Nunes; Abelardo Fernández Chávez; Mathilde Daheron; Xavier Bonfill Cosp; Javier Zamora (BMC, 2019)
Abstract Background Healthcare-associated infections (HAIs) are common and increase morbidity, mortality, and healthcare costs. Their control continues to be an unresolved issue worldwide. HAIs epidemiology shows sex/gender differences. Thus the lack of consideration of sex/gender in Cochrane reviews will limit their applicability and capacity to support informed decisions. This study aims to describe the extent to which Cochrane reviews of interventions for preventing HAIs consider sex and gender. Methods Methodology study appraising Cochrane reviews of interventions to prevent HAIs. Search methods: Cochrane Database of Systematic Reviews from 1995 (launch of the journal) to 31 December 2016. Two authors independently extracted data with EPPI-Reviewer 4 software, and independently appraised the sex/gender content of the reviews with the Sex and Gender Appraisal Tool for Systematic Reviews (SGAT-SR). Results This study included 113 reviews assessing the effects of interventions for preventing HAIs. 100 reviews (88%) used at least one sex or gender-related term. The terminology used was heterogeneous, being "sex" the term used in more reviews (51%). No review defined neither sex nor gender. Thus we could not assess the definitions provided. Consideration of sex and gender was practically absent in the included reviews; in fact, no review met all the applicable items of the SGAT-SR, and 51 reviews (50%) fulfilled no item. No review provided a complete description of the sex and the gender of the samples of the included studies. Only ten reviews (10%) planned to perform sex- and gender-based analysis and only three (3%) could complete the analysis. The method chosen was always the subgroup analysis based on sex (one review) or gender (two reviews). Three reviews (3%) considered sex or gender-related findings in the conclusions. Conclusion Consideration of sex and gender in Cochrane reviews of interventions for preventing HAIs was practically absent. This lack of attention to sex and gender reduces the quality of Cochrane reviews, and their applicability for all people: women and men, boys and girls, and people of diverse gender identities. Cochrane should attempt to address the shortfalls detected.